Design and Analysis of a Formula SAE Car Engine Restrictor - Radzi Ab. Ghani, Amir; Fitri Hassan, M.; Ramly, Ramzyzan (International Journal of Engineering and Technology, 2018)
Formula Society of Automotive Engineers (SAE) is a world renowned automotive design competition that requires engineering students to design and test a single seater race car. The car utilizes a four stroke motorcycle engine with a maximum displacement of 781 cc. The rules require the engine to be restricted using a 20 mm diameter air intake. The challenge is to design an engine restrictor that enables the engine to operate efficiently with minimal power loss despite the significant reduction of volumetric efficiency. The engine restrictor consists of nozzle, plenum (air-box) and runner. CATIA V5 is used to design the restrictor system and ANSYS CFX was used to analyse the air flow. Several nozzle and plenum designs were simulated to determine the best design. It was discovered that the converging nozzle angle, position of restrictor hole inlet and plenum shapes have significant effect on the performance of the restrictor system. Nozzle with converging angle of 18o and inlet hole position of 59.5 mm gave the lowest pressure difference of 8.698 kPa. Engine restrictor Design 3 gave the lowest overall pressure difference of 7.73 kPaÂ